If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 = x + -17 Reorder the terms: 5 = -17 + x Solving 5 = -17 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 5 + -1x = -17 + x + -1x Combine like terms: x + -1x = 0 5 + -1x = -17 + 0 5 + -1x = -17 Add '-5' to each side of the equation. 5 + -5 + -1x = -17 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = -17 + -5 -1x = -17 + -5 Combine like terms: -17 + -5 = -22 -1x = -22 Divide each side by '-1'. x = 22 Simplifying x = 22
| 24=6(5-2a) | | -29=-25+r | | 0=1600-60x | | -9=m-(-5) | | -9/12-(-7/4) | | 7y-3x= | | 15x+(-4x)= | | 1/7*1/6 | | 2xy/5y | | -480=20x | | 4-p=5p+16 | | 522=29x | | 4x+5-2x=-19 | | 3[4x-(2x-7)]= | | a/1/a2= | | 1=v-(-12) | | 5x+12=3x-23 | | 8/9*(-1/8)= | | -3+a=26 | | -5(1+5n)=120 | | (5x+2)(5x-1)=0 | | 3x+y-4x= | | 2(2x-7)+3x=21 | | 3p-6=6 | | -2=n-16 | | 8x+2x-4=126 | | (5x+5)-(2+4x)=5 | | y=3x^2-14x+12 | | 4x+2y+y-9x=25 | | (8x^2-2x-38)+(6x^2+4)=0 | | (-5)2-4(5-3)2= | | 6x^2*4x=0 |